The Importance of Untold and Unheard Stories in Narrative Gerontology: Reflections on a Field Still in the Making from a Narrative Gerontologist in the Making - Blix, Bodil (Narrative Works, 2016)
In this essay, I consider the limitations and possibilities of narrative gerontology. I reflect upon narrative gerontology’s fundamental dependence on people’s narrative willingness. I discuss both the reasons that stories remain untold and the reasons they remain unheard. Furthermore, I suggest that narrative gerontology would benefit from a stronger focus on the act and context of storytelling rather than merely on what is being told. I suggest that narrative gerontology should pay more attention to the diverse sites of engagement, more or less formalized settings, and spontaneous everyday interactions in which older adults tell stories.